Facing West American evangelicals in an age of world Christianity - Swartz, David R. (New York, NY Oxford University Press, 2020)
"The dramatic growth of Christianity around the world in the last century has shifted the balance of power within the faith away from the traditional strongholds of Europe and the United States to the Global South. While we typically imagine Western missionaries carrying religion to the ends of the earth, David R. Swartz shows that the line of influence has often run the other way, as evangelicals in nations such as Korea, India, and Uganda shaped the American church from abroad. Swartz tells stories of evangelicals crossing national boundaries, offering new insights into a tradition that imagines itself as simultaneously American and part of a global communion"--
Includes bibliographical references and index
Keywords: Missions -- History -- 21st century; Evangelicalism -- United States